PENGARUH COUNTRY OF ORIGIN, GREEN MARKETING, BRAND IMAGE, DAN PERCEIVED QUALITY TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MEREK HONDA (Studi Kasus Pada Masyarakat Di Kecamatan Tanjung Kemuning Kab. Kaur) - Apriansyah, Yosef; Sismanto, Adi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
This research is based on the importance of purchasing decisions for business companies. Several factors that influence purchasing decisions are country of origin, green marketing, brand image, and perceived quality. This study aims to determine the effect of country of origin, green marketing, brand image, and perceived quality on purchasing decisions for Honda brand motorbikes. This type of research is quantitative research with a descriptive approach. The research population is the people of Tanjung Kemuning sub-district, Kaur Regency, who use Honda brand motorbikes. The number of research respondents was 110 people, taken using accidental sampling technique. Data collection using a questionnaire. The data analysis technique uses Multiple Linear Regression analysis. Partial test results show that country of origin has a positive and significant effect on purchasing decisions, green marketing has a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions, and perceived quality has a positive and significant effect on purchasing decisions. Keywords: green marketing, brand image, perceived quality, purchasing decisions.